Social scientists as users: searching for recorded sound in its environment - Jahnichen, Gisa; Musib, Ahmad Faudzi (International Association of Sound and Audiovisual Archives, 2013)
For social scientists, it is crucial to access complex information on sound production and the recoring environment. They need data derived from professional recordings that help to support conventional observations. Media distributors have long-held the role of environment sounds as disturbing nuisance that had to be eliminated or suppressed. In the best / worst case, side sounds were left unchanged to create a "lively" atmosphere for an anthropological sound recording or a sound recording for a special audience to which the place of the performance is of particular interest. The coughing in a live concert or the dog barking in the background of a village ensemble became then part of the marketed item. In an archive, sound reductions hopefully not take place. Nevertheless, environmental sound inclusions, in certain recordings, are considered to be side effects of the main recording project undertaken by collectors of different disciplines who did not purposely intended to record those noises. Ideally, they were searching for equipment that avoids it best. Unlike this approach, the project at our institution tries to purposely include all possible environment sounds produced during the primary sound production. These sounds come from various distances and or directions. The paper will focus on the scientific potential and the resonance of these recordings among users in order to achieve more reliable research outcomes. Though small in number, researchers of very different social sciences areas might become a strong and supportive group of future users.